Analysis of Palaeoanthropology of the Sevan Basin of the Middle and Late Bronze Ages Due to the Scientific Works of the Last Century - Mkrtchyan, Ruzan (History and Culture, 2025)
Archaeological biofacts serve as an important historical source for the reconstruction of heritological issues. The similarities and differences of the averaged metric data based anthropological descriptions used to be interpreted in terms of genetic proximity and distance. This approach rooted in Soviet and Armenian anthropology endured over time. The overarching conclusion is the classification of the Bronze Age population of Armenia within the southern European race, yet discord arises in the delineation of specific anthropological traits. The anthropology of the Middle and Late Bronze Age population of the Sevan Basin has the following characteristics: maximal high face, profiliation of nasal bones and maximal vault of cranium. These features differentiate the populace of Gegharkunik region from the paleoanthropological findings not only in Central Asia and the broader Caucasus region, but also from other areas within the Armenian Highlands. The ethnic history of the ancient societies can be reliably reconstructed only if the bio-artifacts under study undergo accurate and detailed historical and social documentation. In contemporary research, ethno-heritage inquiries are increasingly addressed through ancient DNA analyses and comparative studies.  Such investigations involving Armenian materials unveil the remarkable hereditary continuity spanning from the Bronze Age to the modern population.